EVALUATION OF THE DEVELOPMENT OF INDEPENDENCE IN AGRICULTURAL AND LIVESTOCK ACTIVITIES TO PROMOTE FOOD SECURITY AT THE CLASS IIA BATAM CORRECTIONAL INSTITUTION - Muhammad Rafly Firmansyah; Meitissa Vanya Simanjuntak (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to evaluate the implementation of independence training programs through agricultural and livestock activities at the Class IIA Batam Correctional Institution in supporting food security and improving inmates’ skills. The research uses a descriptive qualitative approach with the CIPP (Context, Input, Process, Product) evaluation model, and data were collected through interviews, observations, and documentation. The findings show that, from the context perspective, the program is relevant to national policies and local needs. In terms of input, the program faces constraints such as limited land, budget, and infrastructure. From the process aspect, the activities are carried out in a structured manner, although they are influenced by external factors such as weather conditions and varying levels of inmate motivation. Meanwhile, from the product perspective, the program has produced tangible outputs such as vegetable and fish harvests, while also improving inmates’ practical work skills. Overall, the program contributes positively to both food security within the institution and the development of inmates’ competencies. However, the study is limited to a single correctional institution, so future research is recommended to expand the scope by including comparative analysis across different institutions to obtain more comprehensive insights. Keywords: Independence Development; Food Security; CIPP Evaluation Model